2017
DOI: 10.1097/sap.0000000000001218
|View full text |Cite
|
Sign up to set email alerts
|

Fat Graft Survival After Recipient Site Pretreatment With Fractional Carbon Dioxide Laser

Abstract: Pretreatment of recipient site using fractional CO2 laser helped vascularization in the early stage in fat graft and solved the ischemic condition, so it improved fat survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Several experimental studies have been conducted for recipient site preconditioning in search for improved fat graft survival, including administration of deferoxamine, VEGF, epidermal growth factor, erythropoietin, n‐acetylcysteine. and fractional carbon dioxide laser 13,45–49 . However, most of these modalities have limited clinical application due to their cost, concerns on oncologic safety, difficulties with administration of drugs and thermal damage induced by lasers 50–53 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several experimental studies have been conducted for recipient site preconditioning in search for improved fat graft survival, including administration of deferoxamine, VEGF, epidermal growth factor, erythropoietin, n‐acetylcysteine. and fractional carbon dioxide laser 13,45–49 . However, most of these modalities have limited clinical application due to their cost, concerns on oncologic safety, difficulties with administration of drugs and thermal damage induced by lasers 50–53 .…”
Section: Discussionmentioning
confidence: 99%
“…and fractional carbon dioxide laser. 13,[45][46][47][48][49] However, most of these modalities have limited clinical application due to their cost, concerns on oncologic safety, difficulties with administration of drugs and thermal damage induced by lasers. [50][51][52][53] Flacco et al demonstrated significantly improved fat graft volume retention at eighth week in mice, with preconditioning of the previously irradiated recipient site with deferoxamine, which is an iron-chelator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…87,88 The most common techniques currently being investigated include volume expansion, implantation of alloplastic materials such as silicone, administration of cell-proliferation factors such as VEGF or IL-8, iatrogenic ischemia, and micro-needling. 89–91…”
Section: Recipient Sitementioning
confidence: 99%
“…35,36 Teknik yang paling umum saat ini sedang diselidiki termasuk ekspansi volume, implantasi bahan alloplastic seperti silikon,pemberian faktor proliferasi sel seperti VEGF atau IL-8, iskemia iatrogenik, dan jarum mikro. [37][38][39] Ekspansi volume eksternal adalah metode di mana ekspander eksternal ditempatkan di lokasi penerima. Dalam penelitian pada hewan, telah terbukti meningkatkan tingkat proliferasi cangkok dan jumlah sel akhir, serta jumlah total adiposit dewasa.…”
Section: Situs Penerimaunclassified